TSPO PET Using [18F]PBR111 Reveals Persistent Neuroinflammation Following Acute Diisopropylfluorophosphate Intoxication in the Rat. (17th April 2019) - Hobson, Brad A; Rowland, Douglas J; Sisó, Sílvia; Guignet, Michelle A; Harmany, Zachary T; Bandara, Suren B; Saito, Naomi; Harvey, Danielle J; Bruun, Donald A; Garbow, Joel R; Chaudhari, Abhijit J; Lein, Pamela J
Abstract: Acute intoxication with organophosphates (OPs) can trigger status epilepticus followed by persistent cognitive impairment and/or electroencephalographic abnormalities. Neuroinflammation is widely posited to influence these persistent neurological consequences. However, testing this hypothesis has been challenging, in part because traditional biometrics preclude longitudinal measures of neuroinflammation within the same animal. Therefore, we evaluated the performance of noninvasive positron emission tomography (PET), using the translocator protein (TSPO) radioligand [ 18 F]PBR111 against classic histopathologic measures of neuroinflammation in a preclinical model of acute intoxication with the OP diisopropylfluorophosphate (DFP). Adult male Sprague Dawley rats administered pyridostigmine bromide (0.1 mg/kg, im) 30 min prior to administration of DFP (4 mg/kg, sc), atropine sulfate (2 mg/kg, im) and 2-pralidoxime (25 mg/kg, im) exhibited moderate-to-severe seizure behavior. TSPO PET performed prior to DFP exposure and at 3, 7, 14, 21, and 28 days postexposure revealed distinct lesions, as defined by increased standardized uptake values (SUV). Increased SUV showed high spatial correspondence to immunohistochemical evidence of neuroinflammation, which was corroborated by cytokine gene and protein expression. Regional SUV metrics varied spatiotemporally with days postexposure and correlated with the degree of neuroinflammation detected immunohistochemically. Furthermore, SUV metrics were highly correlated with seizure severity, suggesting that early termination of OP-induced seizures may be critical for attenuating subsequent neuroinflammatory responses. Normalization of SUV values to a cerebellar reference region improved correlations to all outcome measures and seizure severity. Collectively, these results establish TSPO PET using [ 18 F]PBR111 as a robust, noninvasive tool for longitudinal monitoring of neuroinflammation following acute OP intoxication.